2018
DOI: 10.1371/journal.pone.0195262
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin-6 and tumor necrosis factor-α are associated with early graft regeneration after living donor liver transplantation

Abstract: BackgroundLiver graft regeneration is orchestrated by specific and sequential stimuli, including hepatocyte growth factors, cytokines, and catecholamines. We evaluated the association between preoperative serum cytokines and early liver graft regeneration in human living donor liver transplantation (LDLT).Patients and methodsWe retrospectively reviewed the data of adult patients who underwent LDLT from January 2010 to December 2014. Serum cytokines, including interleukin (IL)-2, 6, 10, 12, 17, interferon (IFN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 47 publications
2
20
0
1
Order By: Relevance
“…In the multivariable models, the relationship between cytokines and AT1R-Ab remained consistent when controlling for other clinical variables, and only IL-6 had other significant predictors (aside from time). The additional association of IL-6 with living donation may be reflective of regenerative processes occurring in the allograft, 44 but this relationship requires further investigation. In addition, the cytokines had varying levels during the early posttransplant time point, which may be partially reflective of a proinflammatory state associated with end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the multivariable models, the relationship between cytokines and AT1R-Ab remained consistent when controlling for other clinical variables, and only IL-6 had other significant predictors (aside from time). The additional association of IL-6 with living donation may be reflective of regenerative processes occurring in the allograft, 44 but this relationship requires further investigation. In addition, the cytokines had varying levels during the early posttransplant time point, which may be partially reflective of a proinflammatory state associated with end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Sasturkar et al reported that the peak level of IL-6 and TNF-α were observed on POD 1, the roles of TNF-α and IL-6 were necessary for proper human liver regeneration after partial hepatectomy in healthy liver donors [ 22 ]. Chae et al reported that higher serum IL-6 and TNF-α levels were associated with increased early graft regeneration after living donor liver transplantation [ 23 ]. IL-6 and TNF-α were important mediators in early regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Serial measurements of TNF-α before and after hepatic resection detected only slight elevations, but no correlations with hepatic regeneration [146]. Based on those data, the monitoring of regeneration by TNF-α cannot be recommended [147].…”
Section: Tumor Necrosis Factor Alpha (Tnf-α)mentioning
confidence: 99%
“…Furthermore, a correlation between the peak IL-6 levels and HGF was detected [46]. In the setting of human living donor liver transplantation, higher levels of serum IL-6 were independently associated with increased graft volumes during the first postoperative week [147]. Oyama et al demonstrated that patients with a small graft after living donor liver transplantation showed a higher increase in IL-6 levels postoperatively and a better regeneration rate 2 weeks post-transplant [162].…”
Section: Interleukin 6 (Il-6)mentioning
confidence: 99%